PENGEMBANGAN ALAT TANAM JAGUNG TIPE TUGAL DALAM UNTUK LAHAN KRITIS - Makbul Hajad; Radi Radi; Bambang Purwantana (The University of Lampung, 2021)
Blora and Grobogan are regions with higher production capacity of corn commodity compared to other regions in Central Java province. However, low number of technical irrigation and el-nino phenomenon have become the main threat for the sustainability of corn farming in both regions. During dry session, the top soil of the land are solidified which lead to higher difficulty for planting the corn seed using traditional tool. An improved design of the traditional seeder is then required to solve this problem to enable farmers plant corn seed during dry session. The objective of this research was to develop seeder prototype with “Tugal Dalam” type in Blora and Grobogan regions where the land have been categorized as marginal land during dry session. The proposed design is based on technical, ergonomic, economical, and social aspect. The qualitative approach was used to obtain the technical, ergonomical, economical and social aspect required by the farmer. Kansei Engineering is used to translate and evaluate the proposed design through some tests conducted on several group of farmers where they were requested to use 4 seeder design options and write their preference on each design option based on the mentioned aspects. Tests confirmed that the proposed design can be used to plant a corn seed at farmers desired characteristics. Kansei engineering also confirmed that ‘high speed’, ‘easy to operate’, ‘low price’, ‘easy to handle’ and ‘has a watering system’ were preferred by the farmers and determined their decision on buying and using the seeder tool. Keywords: kansei engineering, marginal land, seeder development, tugal dalam